2019
DOI: 10.1158/1078-0432.ccr-18-3212
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic and Clinical Results from a Phase I/II Study of the HSP90 Inhibitor Onalespib in Combination with Abiraterone Acetate in Prostate Cancer

Abstract: Purpose: Onalespib is a potent, fragment-derived secondgeneration HSP90 inhibitor with preclinical activity in castration-resistant prostate cancer (CPRC) models. This phase I/II trial evaluated onalespib in combination with abiraterone acetate (AA) and either prednisone or prednisolone (P) in men with CRPC progressing on AA/P. Patients and Methods: Patients with progressing CRPC were randomly assigned to receive 1 of 2 regimens of onalespib combined with AA/P. Onalespib was administered as intravenous infusio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A second-generation of SSP90 inhibitors was developed and one of these compounds, Onmalespib, was found to be very active in preclinical models and was beneficial in prostate cancer models expressing AR-V7 [671]. However, in spite this promising preclinical background, Onalespib in combination with Abiraterone failed to show any significant clinical activity in CRPC patients in progression [672].…”
Section: Novel Therapies For Prostate Cancermentioning
confidence: 99%
“…A second-generation of SSP90 inhibitors was developed and one of these compounds, Onmalespib, was found to be very active in preclinical models and was beneficial in prostate cancer models expressing AR-V7 [671]. However, in spite this promising preclinical background, Onalespib in combination with Abiraterone failed to show any significant clinical activity in CRPC patients in progression [672].…”
Section: Novel Therapies For Prostate Cancermentioning
confidence: 99%
“…Hsp90 is a molecular chaperone that is responsible for the folding and function of over 300 “client” proteins involved in prostate cancer development and progression; thus, targeting Hsp90 results in broad inhibition of critical signaling pathways (reviewed in [ 39 , 40 ]). Hsp90 has been extensively investigated as a target in prostate cancer both pre-clinically and clinically [ 41 ], but Hsp90 inhibitors such as 17-AAG and AUY922 have not yet been clinically approved despite continuing efforts [ 42 ]. 17-AAG was the first-in-class Hsp90 inhibitor, and it has far less potency than 2nd generation agents such as AUY922 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Onalespib has been shown in basic studies to block AR nuclear translocation and inhibit its transcriptional activity, inhibiting PCa cell proliferation and tumour growth (Ferraldeschi et al, 2016). In a phase I/II clinical trial, including 48 prostate cancer patients, patients received Onalespib in a phase I/II trial, in which patients were treated with Onalespib in combination with abiraterone acetate, the results showed that no patient exhibited an objective or PSA response, declaring the combination to be unjustified (Slovin et al, 2019). Ganetespib reduced the expression of AKT, AR, IGFR‐1, EGFR, ERK, STAT3 in basic studies and had pro‐apoptotic and tumour growth inhibitory activity (He et al, 2013).…”
Section: Hsp90 and Prostate Cancermentioning
confidence: 99%